Construction engineering in building renovation / Muhammad Farhat Ezral Mizare - Ezral Mizare, Muhammad Farhat (Universiti Teknologi MARA, Perak, 2022)
Civil works is every outcome of building or civil engineering works taken as a whole, which is sufficient of itself to fulfill an economic or technical function and entails one or more elements of a physical infrastructure. The aim of this research is to observe the civil works in building renovation of an existing building in Bandar Baru Bangi, Selangor. The data of the research was collected through observation, interviews, and document reviews. The civil works that were done in the renovation project were construction of clay brick walls, pu grouting waterproofing, construction of concrete bench, skimming, and waterproofing work on roof. Teamwork and communication are key factors for civil works to be done smoothly and fast. Without these two key factors, problems would arise and disrupt the whole project.